1995
DOI: 10.1093/intimm/7.8.1331
|View full text |Cite
|
Sign up to set email alerts
|

CD86 (B70/B7–2) on endothelial cells co-stimulates allogeneic CD4+T cells

Abstract: In vascularized organ transplantation, vascular endothelial cells (EC) confronting recipient T cells are potentially significant APC initiating cellular immune responses that lead to rejection. In the present study, we studied the ability of human EC to stimulate allogeneic T cells and the co-stimulatory molecules involved in this response. On both human umbilical vein endothelial cells (HUVEC) and microvascular endothelial cells (MVEC), MHC class I, intercellular adhesion molecule (ICAM)-1 and CD86 were const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 0 publications
1
30
0
1
Order By: Relevance
“…The role of endothelial cells in initiating a primary T-cell response is important in organ transplantation because the vascular endothelial cells of the allograft are the first target encountered with the recipient's immune system (Marelli-Berg et al, 1996). In vitro experiments showed that the vascular endothelial cells can function as resident APCs to CD4ϩ T cells (Maher et al, 1996;Seino et al, 1995). However, the ability of the endothelium to provide effective costimulatory signals for full T-cell activation was controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of endothelial cells in initiating a primary T-cell response is important in organ transplantation because the vascular endothelial cells of the allograft are the first target encountered with the recipient's immune system (Marelli-Berg et al, 1996). In vitro experiments showed that the vascular endothelial cells can function as resident APCs to CD4ϩ T cells (Maher et al, 1996;Seino et al, 1995). However, the ability of the endothelium to provide effective costimulatory signals for full T-cell activation was controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Another study suggested that the endothelial cells express neither CD80 nor CD86 (Ma and Pober, 1998). However, CD86-dependent costimulation was demonstrated in both the human umbilical vein endothelial cells and a porcine endothelial cell line (Maher et al, 1996;Seino et al, 1995). De Greef et al (2001) found the location of B7-1 (CD80) protein in the endothelial cells of the ascending vasa recta.…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous experiments examining the ability of endothelial cells to express B7 costimulatory molecules have yielded disparate results. [43][44][45] We found that B7-1 was constitutively expressed at a low level on the surfaces of the cloned CVEs, and this level was unaffected by incubation with TNF-␣ (Figure 2). However, B7-1 expression was significantly increased upon stimulation with IFN-␥, and the level was further enhanced by incubation with IFN-␥ and TNF-␣ in combination.…”
mentioning
confidence: 99%
“…In an attempt to study the possible consequences of ␤ cell costimulatory ligand expression, we created and have partially characterized a transgenic mouse expressing murine B7-1 (mCD80) selectively on pancreatic ␤ cells under the rat insulin-1 promoter (RIP) 6 control (10,11). Although these mice rarely develop diabetes spontaneously (Ͻ7% incidence), when disease does occur it has been accompanied by profound insulitis, suggesting an autoimmune pathogenesis (our unpublished observation).…”
mentioning
confidence: 99%